Changing dynamics of global computer software and services industry : implications for developing countries (UN New YorkUS, 2002)
Explores the issues surrounding the development of the computer software and services industry. Examines how intellectual property rights affect their establishment and growth in developing countries. Discusses the implications from that, for policy formulation.
Keywords: COMPUTER PROGRAMS